PENERAPAN PEMBELAJARAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA(PMRI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 124 PEKANBARU - Tuti Handayani; Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This was a classroom research (PTK) which has two cycles which was conducted March-April 2015. The data shown the either learning process increased. The basic score of daily examination as 47,98% which 13 students passed and 17 students failed. The ending of daily examination was 60% and the average was 75,00% on the passing grade. The second daily examination also increased from basic score as 7,67% which 21 students passed and 9 students failed. The ending of second daily examination was 86,67% and the average was 80,75. Based on the explanation above it can be concluded that the implementation of realistic mathematics education (RME) increased students’ achievement the result of science studies of students IV grade of State Elementary School 124 Pekanbaru.Keywords : Realistic Mathematics Education (RME), Students Achievement The Result Of Mathematics Studies